Multilateral Nuclear Cooperation in East Asia; The First Step Toward the Formation of a New Cooperation - 황용수; 권은하; 서은진; 황주호; Yong-Soo Hwang; Eun-Ha Kwon; Eun Jin Seo; Joo-ho Whang (Journal of nuclear fuel cycle and waste technology (Online), 2005)
동아시아 지역에서의 원자력 수요는 경제 발전을 뒷받침하기 위해 급격히 증가하고 있다. 9.11 사태 이후 전 세계적으로 핵비확산은 세계적인 현안이 되고 있으며 이와 함께 타 지 역과는 달리 동아시아 지역에서는 향후 10년 후 몇몇 국가들이 원자력을 새로이 도입하려는 움직임이 있다. 이와 같은 현안에 대처하기 위해 공급 확약과 핵비확산을 목적으로 새로운 지역적인 다자간 원자력 협력 체제가 제안되었다. 이러한 새로운 제안은 신뢰성 증진, 자발적 참여 및 동기 부여의 원칙을 바탕으로 하고 있다. 또한 동아시아에서 다자간 체제를 실행하기 위해 단계적인 접근 방법을 제안하고 있다. Demand on the nuclear energy in East Asian countries has been grown rapidly to support economic development. After 9.11, nuclear security has become the world wide issue. In addition, unlike to other region, some countries are considering the introduction of nuclear power plants. To meet the challenges a new regional multilateral nuclear approach is proposed aiming at assurance of supply and non -proliferation. The new proposal is based on the principles of confidence building, volunteering, and incentives. The step wise approach is recommended to implement the multilateral system in East Asia.